Business and Religiosity: Review of Business Ethics Mayangkara Group - Dedi Suselo (Faculty of Economics, State University of Jakarta., 2018)
This research explores the application of religious values ​​that are a business strategy in the management of the Mayangkara Group. This type of research is descriptive qualitative with a case study approach (field research). Data collection techniques use source, time and technique triangulation. The results show the application of religious values ​​in the management of the Mayangkara Group to be unique and important capital in supporting the existence of the company. A good business management pattern is not to exploit, manage existing natural resources for mutual benefit. Mayangkara Group's religious values ​​are built based on the principles of social piety in every business activity. A series of social, religious, socio-economic activities that are packaged in the company's CSR program is a means of channeling zakat funds and company infaq. The purpose of Mayangkara's business activities is